PENERAPAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE MATEMATIKA UNTUK MENINGKATKAN MOTIVASI SISWA - Lusi Luthfia; Yudi Prasetyo; Erwin Triawan; Muhammad Hanifan; Ripal Anwar; Wahyu Hidayat (Departement of Mathematics Education, 2019)
This study aims to determine the level of student learning motivation towards the application of mathematical example non example learning models. This research is classified as qualitative descriptive which attempts to describe whether the achievement of mathematical reasoning abilities and motivating junior high school students through contrutivism approaches with example non example learning models is better than using learning normal The population of this study were all IX grade junior high school students in Cianjur City. To obtain research data, the instrument was used in the form of a question diagnostic test using the SPSS application and questionnaire (questionnaire) for student academic procrastination.